Kebijakan Dalam Upaya Penanggulangan Stunting Pada Balita Di Kabupaten Solok, Provinsi Sumatera Barat: Effort To Manage Stunting In Children In Solok Regency, West Sumatera Province - Septivani, Rizqa Inatsaa; Arshita, Ditha Arsya; Permana, Alvien Adiwidya (Institut Riset dan Pengembangan Indonesia, 2023)
The problem of stunting is still a serious concern in Indonesia, including in West Sumatra Province. Datafrom Riskesdas 2018 revealed that the prevalence for short and very short children under five in WestSumatra is 30%, and was close to the national prevalence (30.8%). This study aims to describe thesociocultural problems, local potential, and formulate alternative policies in effort to prevent and controlstunting in children under five in Solok Regency. The research design used qualitative methods. Primarydata collection was carried out by in-depth interviews and observations. The technique of selectinginformants was done purposively. The results of the study revealed that the socio-cultural problems inefforts to prevent and control stunting in toddlers are still limited public knowledge about the causes andefforts to prevent stunting, inadequate understanding of the importance of balanced nutritional needs, andthe behavior, parenting patterns, and feeding habits og toddlers who does not support the prevention andcontrol of stunting in children under five. It is recommended that there should be alternative policies andaction plans for stunting prevention, among others, by increasing knowledge through socialization aboutthe risk of stunting on children's intelligence, increase participation and community empowerment forstunting prevention by utilizing the local potential such as curd and bilih fish in Solok Regency, WestSumatera Province.